Studying Same-Sign Top Pair Production through Top-Higgs FCNC Interactions at the HL-LHC - O. M. Ozsimsek; V. Ari; O. Cakir (Advances in High Energy Physics)
We investigate the potential of the HL-LHC for discovering new physics effects via the same-sign top pair signatures. We focus on the semileptonic (electron and muon) decay of the top quarks and study the reach for a simplified model approach where top quark flavor changing could occur through a neutral scalar exchange. A relatively smaller background contribution and clean signature are the advantages of the leptonic decay mode of the same-sign W bosons in the same-sign production processes of top quark pairs. Assuming the FCNC between top quark, up-type quark, and scalar boson from the new physics interactions, the branchings could be excluded of the order O10−4. We use angular observables of the same-sign lepton pairs and the top quark kinematics in the process which provide the possibility of separation of new physics signal from the SM backgrounds using machine-learning techniques. We find that the same-sign top quark pair production is quite capable of testing the top-Higgs FCNCs at the HL-LHC.